Impact of Storyline on Creativity among Middle School Children - George, Kusum Mary; Basavarajappa (INDIAN EDUCATIONAL REVIEW, 2018)
Storyline being a relatively new technique, there are very few studies that have assessed its efficacy in enhancing creativity. The present study focused on the impact of story line as an intervention on enhancing creativity levels among middle school children. Further, the impact of storyline on verbal and nonverbal creativity as well as among the components of creativity with regard to gender was also assessed. The study followed a pre-post intervention experimental design with a control group. Using convenience sampling, 75 students from a single school consisting of 41 boys and 34 girls were evaluated using the creativity assessment test (Mehdi, 1989). Then based on the creativity scores, the children were systematically allotted to the experimental and control group in such a way that both the groups had equal representation of students from all levels of creativity. The experimental group was provided with storyline as an intervention whereas the control group received no intervention. The results reveal that there is a significant difference between the experimental and control group with regard to total creativity scores, verbal creativity, verbal elaboration and verbal originality scores. Results also indicate that storyline enhanced creativity equally among boys and girls.